The prognostic relevance of 14-3-3 expression in cancers: a meta-analysis - Caihong Li; Honglan Zhu; Changlu Liu; Ya Liu; Ting Huang; Daishun Liu (Journal of the Pakistan Medical Association, 2021)
Objective: A number of recent clinical studies have identified a relationship between elevated expressions of 14-3-3 and poorer patient prognosis in the context of several cancers. The present meta-analysis was therefore conducted to gain an enhanced understanding of the prognostic importance of 14-3-3 levels in cancer patients. Methods: Two reviewers independently systematically reviewed the Web of Science, Embase, and PubMed databases to identify published, suitable studies through October 2019. The correlation between the level of 14-3-3 and cancer patient survival were assessed based upon pooled HR (hazard ratios) and 95% CI (confidence intervals) derived from chosen studies. Results: In total we were able to identify 22 eligible studies that had enrolled 2676 patients in the present meta-analysis. Assessment of these studies revealed that elevated 14-3-3 level correlated significantly with poorer OS (overall survival) (HR : 1.93, 95% CI : 1.42-2.61) in cancer patients. This was true even when studies were analyzed in subgroups according to tumor type, sample size, analysis type, and method of HR determination. With respect to disease-free survival (DFS), the pooled HR for cancer patients expressing high levels of 14-3-3 was 1.89 (95% CI: 1.56-2.30). Patients with elevated 14-3-3 expression also exhibited reduced CSS (cancer-specific survival) (HR: 3.47, 95% CI: 2.12-5.69). Conclusions: The outcomes indicate that higher level of 14-3-3 correlates with poorer patient prognosis in a range of cancer types. Keywords: Meta-analysis, Prognosis, 14-3-3 Proteins C Continuous...